Analisis Pengaruh Variasi Aktivator Kimia Pada Karbon Aktif Kayu Sengon Untuk Pengolahan Filtrasi Air Asam Tambang - Riza Hudayarizka; Raudiah Tuzzahra Putri; Mochammad Purwanto; Ismi Khairunnissa Ariani (LPPM ITK, 2025)
Acid mine drainage is one of the major pollutants generated from coal mining activities, characterized by high concentrations of heavy metals such as Fe and Mn and very low pH levels, making it unsuitable for environmental discharge. This study aims to analyze the effect of different chemical activators (NaOH, H₃PO₄, HCl, and no activator) on the effectiveness of activated carbon made from sengon wood in removing contaminants from acid mine drainage. The carbonization process was carried out at high temperatures, followed by chemical activation and application as filtration media. The results showed that unactivated carbon provided the highest TSS removal efficiency at 65.79% and increased the pH to 2.7. However, all variations of activated carbon were ineffective in removing Fe and Mn, likely due to the low initial pH causing protonation of functional groups on the carbon surface, thus reducing their adsorption capacity. This study indicates that while chemical activation influences the characteristics of activated carbon, it is not yet sufficient for optimal removal of heavy metal pollutants.